Business Feasibility of LNG Distribution for Nias Gas Power Plants Using MCDM - Brama Halilintar; Asep Handaya Saputra; Wisnu Isvara (Jurnal Sosial Teknologi, 2026)
Nias Island represents an isolated power system in Indonesia that still relies heavily on diesel-based generation, resulting in high operational costs and greenhouse gas emissions amid Indonesia’s national energy transition toward Net Zero Emissions targets. Liquefied Natural Gas (LNG) is considered a transitional fuel to improve energy security and environmental performance in remote regions. This study aims to evaluate the business feasibility and infrastructure selection of LNG distribution for the Nias Gas Engine Power Plant by comparing an onshore terminal and a mini–Floating Storage Regasification Unit (FSRU). A quantitative decision-making approach using Multi-Criteria Decision Making (MCDM) with the Analytic Hierarchy Process (AHP) was applied, integrating technical, economic, and environmental criteria. Economic analysis includes NPV, IRR, and payback period, while environmental assessment follows IPCC 2006 emission guidelines. Findings show both alternatives are financially viable under an LNG price assumption of USD 7/MMBtu, with the FSRU generating higher NPV and IRR, while the onshore terminal demonstrates superior reliability and lower emissions. The study concludes that although both schemes are feasible, the onshore terminal is slightly preferred due to its stronger reliability and environmental performance, making it more aligned with long-term energy transition goals. Policy implications support Indonesia energy transition agenda acceleration